VARIASI KONSENTRASI PEREKAT PATI SAGU TERHADAP KARAKTERISTIK BRIKET BIOARANG SABUT KELAPA - Suherman Artha; Faizah Hamzah; Farida Hanum Hamzah (Jurnal Online Mahasiswa (JOM) Bidang Pertanian, 2019)
Increasing need of energy and decreasing of fuel supply, requires human to discover alternative energy resources. Consequently, there should be a research to discover a new renewable energy source such as coconut fiber waste. Coconut fiber are mostly the least used waste from coconut fruit as an alternative energy resources. The method of this research used Completely Random Design (CRD) which consist of 5 treatment and each treatment was repeated 3 times. The treatment was P1 = 96% charcoal flour: 4% adhesive, P2 = 94% charcoal flour: 6% adhesive, P3 = 92% charcoal flour: 8% adhesive, P4 = 90% charcoal flour: 10% adhesive, and P5 = 88% charcoal flour: 12% adhesive. Based on analitycal result of coconut fiber leaves charcoal briquet research, the best quality briquet is the P1 concentration of coconut fiber charcoal is 96% charcoal flour: 4% adhesive, had 7,75% water content, 17,09% ashes content, 72x 10-3 g/s combustion rate, 16,13%evaporated substance rate, 59,02% carbon rate, and 4.704 cal/g heat value.